(untitled) (SAARC Journal of Agriculture, 2016)
The study was conducted to establish the Sterile Insect Technique (SIT) method of controlling oriental fruit fly, Bactrocera dorsalis (Hendel). The sterile male ratio of oriental fruit fly was optimized for possible field application of Sterile Insect Technique. Several batches of 5 and 6-dayold pupae were irradiated at 30, 40, 50 and 60 Gray (Gy) to optimize the radiation dose of sterilization. Highest pupal duration and abnormal adults were found after imposing gamma radiation in 5-day-old pupae treated with 60 Gy dose. Radiation significantly increased the nonemergence percentage and decreased the normal emergence of oriental fruit fly. The sterilizing doses were recorded as 60 Gy for 5-dayold pupae. Fixed number of virgin females of oriental fruit flies were allowed to mate with unirradiated and irradiated males at 1:1, 1:2, 1:5 and 1:9 ratios in different cages to find out the rate of suppression against wild population. Minimum pupal recovery and percent normal emergence observed at 1:9 ratio. Deformed and undeveloped (not emerged) population increased with the ratio of irradiated males. The 1:9 ratio was found as the best for suppression of wild population of B. dorsalis. SAARC J. Agri., 13(2): 50-60 (2015)